Morfogénesis in vitro a partir de yemas apicales y bases de hojas de las especies de bromelias Aechmea veitchii y Racinaea crispa (2011)
ABSTRACT: The bromeliads are a promissory resource in our Neotropical forests. However, due to their uncontrolled harvest and the devastation of their habitats, some populations of these plants have declined drastically to the point that many are threatened with extinction. Thus, ef cient propagation techniques such as tissue culture constitute an aid to conservation and sustainable management strategies for these resources, as in the case of Aechmea veitchii Baker and Racinaea crispa Baker. To this end, leaf segments of eld plants, and apical buds and leaf segments of plantlets cultured in vitro, were used as explants. The effect of different combinations and concentrations of auxin and cytokines on callus formation, type of callus and shoot regeneration were evaluated, using MS medium with half and complete salt concentrations as basal medium. Results showed that there was no response when using explants from eld plants; however, in vitro seedlings, adventitious buds were developed on the apical buds of A. veitchii, in MS medium with IBA (1.0 mg/l), TDZ (0.5, 1.0, 1.5 and 2.0 mg/l) with IBA (0.1 mg/l) and BAP (5.0 mg/l) with ANA (0.2 mg/l) induced malformed buds and shoot clusters. A low percentage of adventitious shoots and bud clusters were obtained from the basal region of the young leaves of A. veitchii; however, in MS medium supplemented with kinetin and 2,4D nodular, callus formation was obtained. In vitro propagation of R. crispa from seeds was possible, but its response to the growth regulators evaluated was poor and no plants were regenerated.